Audit and Feedback to Improve Laboratory Test and Transfusion Ordering in Critical Care: A Systematic Review & Assessment of Adherence to Best Practices - Foster, Madison (Université d'Ottawa / University of Ottawa, 2019)
Audit and feedback (A&F), provision of performance data, can be an effective means to change behaviour. We hypothesize that A&F may be useful in the complex environment of critical care to address routine ordering behaviours. This thesis describes a systematic review assessing the use and effectiveness of A&F for the improvement of intensive care unit laboratory test and transfusion ordering and an analysis of how these interventions adhere to recent suggestions for best practice. The review identified relatively few published studies, almost all of which involved multi-component interventions; these were generally found to be moderately effective. Through development of an evaluation tool, we found recent suggestions for best practice may be underutilized in existing A&F interventions. This work has identified several priorities for future research to aid in the optimization of critical care A&F interventions aimed at improving test and transfusion ordering.
Keywords: Audit; Feedback; Critical Care; Intensive Care Unit; Laboratory; Test; Transfusion